First record of True's beaked whale Mesoplodon mirus in New Zealand. (10th January 2014) - Constantine, Rochelle; Carroll, Emma; Stewart, Ramari; Neale, Don; van Helden, Anton
Abstract : On 27 November 2011, a whale resembling a True's beaked whale, Mesoplodon mirus, was found stranded on the South Island of New Zealand. Sequencing of two mitochondrial regions (cytochrome b and mtDNA control region) confirmed species identification as a True's beaked whale that was genetically identified as female. Further examination of the carcass found that the whale was pregnant although decomposition excluded determination of the age of the foetus. This specimen is confirmed as the first record of the species in New Zealand further supporting New Zealand as a whale stranding hotspot.